2019
DOI: 10.3389/fgene.2019.00623
|View full text |Cite
|
Sign up to set email alerts
|

Weighted Fused Pathway Graphical Lasso for Joint Estimation of Multiple Gene Networks

Abstract: Gene regulatory networks (GRNs) are often inferred based on Gaussian graphical models that could identify the conditional dependence among genes by estimating the corresponding precision matrix. Classical Gaussian graphical models are usually designed for single network estimation and ignore existing knowledge such as pathway information. Therefore, they can neither make use of the common information shared by multiple networks, nor can they utilize useful prior information to guide the estimation. In this pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 62 publications
1
5
0
Order By: Relevance
“…The GGM has also been modified to integrate biological knowledge. In the modified version of the GGM, lasso is frequently used for the estimation of partial correlations between genes [87][88][89][90]. Most of these methods, including weighted graphical lasso [87], information-incorporated GGM, prior lasso [88], graphical adaptive lasso [89], and fused pathway graphical lasso [90], use a weight matrix that assigns weights to the links between the genes based on prior biological information.…”
Section: Integration Of Heterogeneous Data Sources For Gene Regulatory Network Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…The GGM has also been modified to integrate biological knowledge. In the modified version of the GGM, lasso is frequently used for the estimation of partial correlations between genes [87][88][89][90]. Most of these methods, including weighted graphical lasso [87], information-incorporated GGM, prior lasso [88], graphical adaptive lasso [89], and fused pathway graphical lasso [90], use a weight matrix that assigns weights to the links between the genes based on prior biological information.…”
Section: Integration Of Heterogeneous Data Sources For Gene Regulatory Network Estimationmentioning
confidence: 99%
“…In the modified version of the GGM, lasso is frequently used for the estimation of partial correlations between genes [87][88][89][90]. Most of these methods, including weighted graphical lasso [87], information-incorporated GGM, prior lasso [88], graphical adaptive lasso [89], and fused pathway graphical lasso [90], use a weight matrix that assigns weights to the links between the genes based on prior biological information. These methods have been validated for gene expression data of liver, lung, ovarian, and breast cancers and were found to perform better than the benchmark methods.…”
Section: Integration Of Heterogeneous Data Sources For Gene Regulatory Network Estimationmentioning
confidence: 99%
“…However, its performance may be improved by utilizing the network similarity across the related conditions. As such, joint graphical modeling is preferred (Danaher et al, 2014;Oates et al, 2014;Chun et al, 2015;Yang et al, 2015;Haslbeck and Waldorp, 2015;Cai et al, 2016;Qiu et al, 2016;Hallac et al, 2017;Huang et al, 2017;Lyu et al, 2018;Zhu and Koyejo, 2018;Lee et al, 2018;Geng et al, 2019;Jia and Liang, 2019;Zhang et al, 2019;Wu et al, 2019Wu et al, , 2020.…”
Section: Introductionmentioning
confidence: 99%
“…As the changes of regulatory relationships between two different states is more likely to occur between genes that are known to have regulatory interactions, considering prior gene regulatory interactions may help to improve the accuracy of differential network estimation. Moreover, researchers have found that genes within same pathways usually interact with each other to carry out their biological functions, and genes belong to different pathways seldom interact with each other ( Wu et al, 2019 ). Thus, taking into account pathway information may also facilitate the inference of differential networks.…”
Section: Introductionmentioning
confidence: 99%